Uses of reflector amplitude of seismic acoustic impedance logs as an aid in deducing lithological content of the geological formations - Almayahi, A.Z. (Mesopotamian Journal of Marine Sciences, 2022)
Seismic data of two across lines have been processed. The processing sequence implied a suggested parameters that have least effects on original wavelet attributes (e.g., the amplitude and shape). This processing procedure is a legitimate enough for studying the lithological consists of geological formations as well as hydrocarbon contents. A total of 47 wiggle traces (i.e., 19 wiggle traces from line one and 28 wiggle traces from line two) have been aligned side by side according to their CDP number. The data were limited to time window of 1000-2000 m sec. Reflector amplitudes were manually picked/estimated along the all seismic wiggle traces. The picked amplitude values were plotted as contour maps. Contour maps provided preliminary indications of lithological variation from soft to hard physical properties within the formation where seismic line crosses. A number of contour lines closures in line one were noticed. These closures may be an indication of variation in the lithological consistent and hydrocarbon trap. More contour lines closures were existed in the second line. Some of them were new and the other were extension to the closure in the first line. These closures/features can be a horizontal extension to the same facies.